Evaluation of mutation effects on UGT1A1 activity toward 17beta-estradiol using liquid chromatography-tandem mass spectrometry - Wada, Keiko; Takeuchi, Atsuko; Saiki, Kayoko; Sutomo, Retno; Van Rostenberghe, Hans; Yusoff, Narazah Mohd; Laosombat, Vichai; Sadewa, Ahmad Hamim; A.Talib, Norlelawati; Yusoff, Surini; Lee, Myeong Jin; Ayaki, Hitoshi; et al. (2006)
Mutations in the gene encoding UDP-glucuronosyltransferase 1A1 (UGT1A1) may reduce the glucuronidation of estradiol, bilirubin, etc. In the present study, we used a liquid chromatography-tandem mass spectrometry (LC/MS/MS) method to assay the activities of recombinant mutated UGT1A1 toward 17beta-estradiol (E2), by determining its glucuronide (E2G) content. Direct evidence for glucuronide formation was provided by E2G-specific ion peaks. The UGT1A1 activities of G71R (exon 1), F83L (exon 1), I322V (exon 2) and G493R (exon 5) mutants were 24, 30, 18 and 0.6% of the normal UGT1A1 activity, respectively. In conclusion, our study showed that LC/MS/MS enabled accurate evaluation of the effects of mutations on recombinant UGT1A1 activity towards E2.